Geographical variation in Tylencholaimus mirabilis (Nematoda: Tylencholaiminae) evidence from South African and Indian populations - Shokoohi, Ebrahim; Ahmad, Wasim; Islam, M. Niraul; Masoko, Peter (Zootaxa, 2026)
Understanding intraspecific variation in nematodes is essential for accurate taxonomy and ecological interpretation. This study examined morphological and molecular variation in Tylencholaimus mirabilis from geographically distinct populations in South Africa and India using an integrative taxonomic approach. South African populations from Limpopo Province were studied using light microscopy (LM), scanning electron microscopy (SEM), and partial sequencing of 18S and 28S rDNA for morphological characterization and phylogenetic placement. Comparative morphometric analyses were conducted using PCA, PCoA, and UPGMA. South African specimens showed a slender body (768–977 μm), cap-shaped lip region, longer posterior genital branch (4–17 μm), and longer odontostyle (6–9 μm), whereas Indian population had a stouter body with shorter posterior branch (6–9 μm) and odontostyle (6.5–7.5 μm). Multivariate analyses confirmed morphological separation supported by Euclidean distances and cophenetic correlation values. Phylogenetic analyses of 18S and 28S rDNA confirmed species identity and revealed close relationships among populations from South Africa, the Netherlands, and India with strong support (posterior probabilities 0.93–1.00). Combined morphological, statistical, and molecular evidence demonstrated geographic differentiation within T. mirabilis, highlighting the importance of integrative approaches in resolving intraspecific diversity and improving nematode taxonomy.